Sexual Activity, Psychosexual Distress, and Fear of Progression in Women with Human Papillomavirus-Related Premalignant Genital Lesions. Issue 2 (1st February 2016) - Nagele, Eva; Reich, Olaf; Greimel, Elfriede; Dorfer, Martha; Haas, Josef; Trutnovsky, Gerda
ABSTRACT: Introduction: Genital human papillomavirus (HPV) infections are very common in women 18 to 30 years old and substantially affect women's sexual health. Aim: To examine sexual activity, psychosexual distress, and fear of progression in women diagnosed with HPV-related precancerous genital lesions. Methods: In this observational study, women diagnosed with premalignant lesions of the cervix, vagina, or vulva were recruited from a university hospital–based colposcopy clinic. Main Outcome Measures: Quantitative data from three validated patient-administered questionnaires (Sexual Activity Questionnaire, German version of the Cervical Dysplasia Distress Questionnaire, and Fear of Progression Questionnaire) were compared within the study population, according to the location of the genital lesion, and with relevant reference populations. Qualitative data from two written open-ended questions about women's thoughts regarding diagnosis and information were analyzed. Results: Two-hundred nine women completed the questionnaires. Seventy-eight percent of women (n = 162) were referred for evaluation of suspect lesions of the cervix, 8% (n = 17) of the vagina, and 14% (n = 30) of the vulva. There were no significant differences in questionnaire results among the three patient groups, except for sexual consequences (Cervical Dysplasia Distress Questionnaire) and recent sexual activity (Sexual Activity Questionnaire). Women with vulvar lesions were most likely to worry about sexual consequences (ie, being unable to have children, being sexually less attractive, or infecting a sexual partner; P = .04). The Sexual Activity Questionnaire subscales sexual pleasure ( P = .15) and sexual habits ( P = 1.00) were similar to those in a healthy control population, whereas sexual discomfort ( P = .51) was comparable to that in a reference population of women who survived cervical cancer. The subscale partner-specific concerns (Fear of Progression Questionnaire) was similar to that in a reference population of patients with cancer ( P = .28). Conclusion: HPV-related precancerous genital lesions, especially of the vulva, are likely to cause concerns about sexual health. Effective information and communication are important to lessen negative sexual consequences and anxiety.